As relações da tríplice hélice no setor da carcinicultura do Rio Grande do Norte: uma análise a partir das abordagens da imersão social e da dependência de recursos - Silva Filho, Roosevelt Bezerra da (2009)
This work consists in a study of the Shrimp Industry in the state of Rio Grande do Norte, whose central issue relates to the understanding of how the Triple Helix (University, Government and the productive sector) interrelationship limits or expands the industry s innovation process. The study aims to understand how the Triple Helix relationship interferes in the innovation process of shrimp in Rio Grande do Norte. As the knowledge becomes the resource key for production methods, the generation of new technologies, new products and processes which demands joint and integrated action of the institutions comprising the Triple Helix: University, Government and productive sector, which possess the essential resources to innovate the process and can be maximized from cooperative relationships between the referred Institutions. Thus, in this work, it was sharply used the pioneering studies of Sabato and Botana (1968) regarding the cooperation relationship between the scientific-technological sphere, the governmental and the productive base, and studies on the Triple Helix approach, proposed by Etzkowitz and Leydesdorff (2000), in which the university has a key role in the process of technological and innovative development of countries and regions, and under which it is assigned to the very University - the character of the entrepreneurial institution, through the concept of entrepreneurial University. Aiming to overcome the criticism of Cooke (2005), regarding the limitations of the Triple Helix approach, in this study it was used - as analytical perspectives - the perspective of social immersion (Granovetter, 1985, 2005) and the theory of resources dependence (PFEFFER; SALANCIK, 1978). The analytical perspectives presented in here, despite of the different assumptions, are essential to eliminate the bias that one only approach can lead (ASTLEY; VAN DE VEM; 2007). The authors arguments focus on the fact that the integration is possible if the researcher acknowledged that different perspectives may have different descriptions of the same phenomenon. As a research strategy, this study is characterized as a study case, along with the proposed objectives - the qualitative method was used as an approach and, depending on the gathering of the sector s historical, a sectional longitudinal view approach was applied (VIEIRA, 2004). The primary and secondary data were used in order to understand the sector s evolutionary process and its inter-institutional relations - regarding the shrimp culture in Rio Grande do Norte - to promote the development, as the content was used for the technical analysis (BARDIN, 1977). The approach of social immersion and resources addiction dependence made it possible to understand that relationships are established within and between each sphere (university, government and productive sector) characterizing a network of low density relationships and strongly internal and external dependence. Based on the speech of Etzkowitz and Mello (2006), a successful Triple Helix strategy of innovation requires not only the involvement and commitment of the parts, within the institutional sphere and among them, but also the development of mechanisms to coordinate the multiple and complex interactions and interfaces, focusing on promoting both environment and context for innovation and learning; it can be acknowledge from study results that the shrimp in the State of the RN, although there are several institutional mechanisms to promote greater integration and technological development, has been presented disjointed - both internally and between the spheres - and under no legitimate practice when facing the innovational promotion and integration institutions. Due to those factors, the central institutions of the network are crucial to the promotion of innovations, spreading through their direct contacts the importance factor of the sustainable competitive activity in the world market and on the national level. However, it may be concluded, from the data, that the Triple Helix relations are interfering in a negative way on what concerns the promotion of innovations in the shrimp industry in RN